Collaborative research methods in the Arctic : experiences from Greenland - Merrild, Anne; Ren, Carina (London ; New York : Routledge, 2021)
This book addresses the growing demand for collaborative and reflexive scholarly engagement in the Arctic directed at providing relevant insights to tackle local challenges of arctic communities. It examines how arctic research can come to matter in new ways by combining methods and engagement in the field of inquiry in new and meaningful ways. Research informs decisions affecting the futures of arctic communities. Due to its ability to include local concerns and practices, collaborative research could play a greater role in this process. By way of example of how to bring new voices to the fore in research, this edited collection presents experiences of researchers active in collaborative arctic research. It draws multidisciplinary perspectives from a broad range of academics in the fields such as law and medicine over tourism and business studies, planning and development, cultural studies, ethnology and anthropology. It also shares personal experiences of working in Greenland and with Greenlanders, whether communities, businesses and entrepreneurs, public officials and planners, patients or students. Offering useful insights into the current problems of Greenland representative of the arctic region, this book will be beneficial for researchers and scientists involved in arctic research.
Collaborative research methods in the Arctic: why and how? -- Telling the good story: a conversation with Minik Rosing on research collaboration and research in Greenland -- Participatory principles and privileges in Arctic health research -- Arctic auto-ethnography: unsettling colonial research relations -- Industrial development in Nuuk and Sermersooq: empowerment through action research -- Collaboration to secure relevance and quality in a study of EIA practise in extractive industries in the Arctic -- Critical proximity in Arctic research: reflections from the Arctic Winter Games 2016 -- Life Mapping: s collaborative approach to tourism collaboration in Greenland -- Developing jurisprudence research through the engagement of students -- Recruiting and retaining labour in Greenland: a PhD project in close cooperation with local stakeholders -- Co-creating knowledge for and with the Arctic: future avenues -- Index.
OCLC-licensed vendor bibliographic record.
Keywords: Greenland -- Research; Arctic regions -- Research; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography